The Estimation of Genetic Parameters of Cucumber Fruit Yield components (Cucumis sativus L.) - Harumi Farah Setyaningastuti; Taryono Taryono (Agrotechnology Innovation Center, Universitas Gadjah Mada, Yogyakarta, 2019)
Cucumber is regarded as main vegetable in Indonesian, however its production cannot match the demand and to increase production can be done by increasing diversity and productivity through plant breeding. The estimation of genetic parameters plays an important role in breeding work, therefore the objectives of this study were to obtain the estimated value of the genetic parameters of some cucumber yield components, to determine the important characteristics of cucumber yield components, and to identify cucumber accessions with high potential yield. The study was conducted at AIC UGM, Berbah, Sleman, Yogyakarta. The accessions used were 23 numbers from the AIC UGM collections and 4 controls. The study used a completely randomized design and analyzed with ANOVA. The results showed that the days to ﬁrst harvest, fruit length, fruit weight, fruit diameter, and ﬂesh thickness give high heritability. The number of fruits and potential yield per hectare gives moderate heritability, and seed rendement gives low heritability. Fruit weight, fruit breadth, and ﬂesh thickness were found as the main important characteristics in yield component. Accession number 372 has the earliest ﬁrst harvest date, accession number 329 and 390 have high potential yield/hectare, fruit weight, fruit length, ﬂesh thickness, and fruit breadth.